Numerical and experimental investigation on thermal performances of quartz tube gravity-driven solid particle solar receiver based on linear-focused solar furnace. (February 2023) - Yu, Yupu; Bai, Fengwu; Wang, Zhifeng
Abstract: This paper reported a novel quartz tube gravity-driven SPSR. A test platform of the receiver with a drop length of 4 m based on a linear-focused solar furnace was built. The optical performances of the linear-focused solar furnace were measured by a direct method. Solid particles were heated to a temperature of 156 ∼ 308 °C after a single pass with an averaged irradiance of 14.9 ∼ 21.7 k W / m 2 . A three-dimensional mathematical model with the wavelength dependent radiative properties integrated is built and discretized in OpenFOAM, which is later verified by experimental results. Lastly, the influences of several pertinent parameters on thermal performances of the receiver are studied using the proposed model. It was observed that the green-house effect of the quartz tube could reduce the radiative heat losses by a percentage from 2.1% to 9.4%. Wind speed surrounding the quartz tube has a positive effect on the green-house effect since high wind speed is helpful to decrease the outer surface temperature of the tube. An optimal thermal efficiency of 57.2% was obtained when heating particles from 27 °C to 800 °C by circulating particles for four times. The proposed model could be used for the design and optimal operation of the quartz tube gravity-driven SPSR.